Impact of Urban Lighting on Insects: A Legal Perspective on Environmental Concerns - P., Bhattacharyya; K., Banerjee; S., Adhikary (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Light pollution, a result of excessive and improperly directed artificial lighting, has become a major environmental issue that affects a wide range of habitats. The spread of industrialization and urbanisation leads to an increase in artificial light's incursion into natural habitats, which modifies the behaviours and ecological dynamics of creatures. Insects are so important to the functioning of ecosystems, the impacts of Artificial Light at Night on insect populations have received a lot of attention. Recognising the urgent need to address the adverse impacts of light pollution on vital insect populations, this study aims to explore the effect of artificial light on insect mortality. Every morning, dead insects were gathered. The insects were drawn to the light source that was circling it during the experiment, but they eventually lost their path and perished tragically. Increased insect mortality throws off feeding chains, pollination, nutrient cycles, and other crucial ecological activities. In order to prevent light pollution from having a negative influence on these vital insect populations, conservation methods must be specifically targeted. The increasing urban lighting exacerbates light pollution, significantly impacting insect populations. This paper examines the ecological consequences and the role of environmental law in mitigating these effects, advocating for stricter regulations and sustainable lighting practices to preserve biodiversity and ecological balance. Key international environmental laws addressing light pollution include the Convention on Biological Diversity (CBD) and the European Union's directives on environmental protection. These laws emphasize the need for sustainable urban lighting practices to protect biodiversity and mitigate the adverse effects on insect populations.